School refusal, depression and suicidality in an adolescent girl- the interplay of stress and vulnerability: a case report - Thakur, Anita; Chauhan, Nidhi; Padhy, Susanta (International Journal of Research in Medical Sciences, 2019)
The stress vulnerability model emphasizes the interplay of genetic vulnerability, personal characteristics and psychosocial factors in the causation of mental illness. The index case highlights the genesis of psychiatric illness in an adolescent female with a family history of bipolar disorder and substance dependence leading to impaired family interaction and family dynamics. Individual psychotherapy, family therapy and pharmacological management proved beneficial in the index case.